Facilitating English Grammar Learning by a Personalized Mobile-Assisted System With a Self-Regulated Learning Mechanism - Wang, Xiao; Chen, Jing; Zhang, Tingting (Frontiers in Psychology, 2021)
This study developed a personalised mobile-assisted system with a self-regulated learning (SRL) mechanism to facilitate English-as-a-foreign-language (EFL) students’ learning of grammar. A quasi-experimental design, involving an experimental group (n = 278) and a control group (n = 320), was adopted to examine its effectiveness on students’ grammar learning. The experimental group, who had full access to the functions of the system (i.e., recommendations, feedback and an e-portfolio package), used the system to learn grammar, complete grammar exercise, and engage in for a semester, while the control group only use the system to submit weekly assignments. The results suggest that the experimental group obtained significantly higher scores in English grammar tests than the control group and the system benefitted both genders with no significant differences. The findings provide empirical evidence in support of the effectiveness of this system in improving students’ grammar test scores, indicating its value as a supplementary tool to conventional classroom teaching of English grammar via supporting learners’ SRL development in a m-learning context. The pedagogical implications for applying this system in classrooms and beyond were discussed.